The Influence of Leadership and Discipline on Work Motivation and Its Impact on the Performance of Employees at the Office of Cooperatives, UKM, Industry and Trade, Bungo Regency - Wahyu Aldino; Astuti Prihatiningsih (International Journal on Advanced Science, Education, and Religion, 2022)
The purpose of this study was to examine the influence of leadership, discipline, motivation and performance. The influence of leadership, discipline, motivation and performance of employees tested either directly or indirectly. To examine issues directly above the survey conducted by distributing questionnaires to employeesof the industry and trade SME cooperative service officeof Bungo. Data was analyzed by path analysis. The results of this study indicate that the leadership, discipline and work motivation influence simultaneously and partially on performance.Where is the leadership, discipline, motivation and performance of employees at the SME cooperative service office of the industry and trade, where are the good categories, Discipline are in both categories, motivation and performance of employees are in both categories.The analysis tool in this research uses descriptive method verification. Where is the use of a range of scales, while in the verification using path analysis or path analysis.